Academic fraudulence in online degrees and exams at Australian universities - E, Smith; L, Clarke,; P, Carmona,; S, Cerimagic, (IJRDO- Journal of Educational Research, 2017)
In recent years an ever increasing number of universities have started to offer online degrees.In Australia most universities offer online degrees, there however currently there is oneleading online higher education provider, which this study will be referred to as ‘onlinedegree providers’ (ODP).Along with this new method of completing degrees comes new forms of academic dishonestyand misconduct. Academic dishonesty and misconduct among students is not a newphenomenon. Brimble and Stevenson-Clarke (2006) find that not only is academic dishonestywidespread, it is also often underestimated by universities. Additionally, researchers havefound that technology has enabled students to cheat in a number of different ways (Etter etal., 2006; Devlin and Gray, 2007; Howard and Davies, 2009). For example, students now canaccess information online via their phones while sitting in a closed-book exam (Kuntz Butler,2014).This paper contributes to the limited research literature on academic dishonesty andmisconduct in online programs and online exams at Australian universities by taking a closelook at what academic dishonesty and misconduct is and how it is happening. It is importantthat these questions be understood because, students who cheat at university are more likelyto become professionals who in the future will engage in illegal, unethical or immoralbehaviours in the workplace. Even though this paper considers academic dishonesty broadly,the focus of the paper is on cheating in online exams.